Dapagliflozin versus empagliflozin in patients with chronic kidney disease - Alnsasra, Hilmi; Tsaban, Gal; Solomon, Adam; Khalil, Fouad; Aboalhasan, Enis; Azab, Abed N.; Azuri, Joseph; Hammerman, Ariel; Arbel, Ronen (Frontiers in Pharmacology, 2023)
Background and Aim: Dapagliflozin and empagliflozin have demonstrated favorable clinical outcomes among patients with chronic kidney disease (CKD).However, their comparative monetary value for improving outcomes in CKD patients is unestablished. We examined the cost-per-outcome implications of utilizing dapagliflozin as compared to empagliflozin for prevention of renal and cardiovascular events in CKD patients.Methods: For calculation of preventable events we divided the allocated budget by the cost needed to treat (CNT) for preventing a single renal or cardiovascular event.CNT was derived by multiplying the annualized number needed to treat (aNNT) by the annual therapy cost. The aNNTs were determined based on data from the DAPA-CKD and EMPEROR-KIDNEY trials. The budget limit was defined based on the threshold recommended by the United States' Institute for Clinical and Economic Review.